Catalogue of inherited disorders found among the Irish Traveller population. Issue 4 (22nd January 2018) - Lynch, Sally Ann; Crushell, Ellen; Lambert, Deborah M; Byrne, Niall; Gorman, Kathleen; King, Mary D; Green, Andrew; O'Sullivan, Siobhan; Browne, Fiona; Hughes, Joanne; Knerr, Ina; Monavari, Ahmad A; et al.
Abstract : Background Irish Travellers are an endogamous, nomadic, ethnic minority population mostly resident on the island of Ireland with smaller populations in Europe and the USA. High levels of consanguinity result in many rare autosomal recessive disorders. Due to founder effects and endogamy, most recessive disorders are caused by specific homozygous mutations unique to this population. Key clinicians and scientists with experience in managing rare disorders seen in this population have developed a de facto advisory service on differential diagnoses to consider when faced with specific clinical scenarios. Objective(s) To catalogue all known inherited disorders found in the Irish Traveller population. Methods We performed detailed literature and database searches to identify relevant publications and the disease mutations of known genetic disorders found in Irish Travellers. Results We identified 104 genetic disorders: 90 inherited in an autosomal recessive manner; 13 autosomal dominant and one a recurring chromosomal duplication. Conclusion We have collated our experience of inherited disorders found in the Irish Traveller population to make it publically available through this publication to facilitate a targeted genetic approach to diagnostics in this ethnic group.